OVERCOMING ANXIETY CHRONIC KIDNEY FAILURE PATIENTS WITH SPIRITUAL MINDFULNESS INTERVENTION: A CASE STUDY - MAHYUVI, TATA; Sari, Novita (Nursing Sciences Journal, 2023)
ABSTRACT Chronic kidney failure sufferers experience many changes in their lives, including changes in diet management, exercise, control of blood sugar, urea, creatinine and kidney function replacement therapy, so they are prone to experiencing anxiety. The aim of this case study is to carry out nursing care to overcome anxiety problems in kidney failure patients with spiritual mindfulness intervention in the Inpatient Room of the Surabaya A.Yani Islamic Hospital. This type of research is a qualitative method with a case study approach. The subjects used were 1 patient with chronic kidney failure who was being treated at the Surabaya A. Yani Islamic Hospital with anxiety problems. Nursing care includes: assessment, determining a diagnosis, making interventions, implementation and evaluation. The implementation, which was carried out to overcome anxiety with spiritual mindfulness interventions, was carried out for 3 days (2 times a day for 10-15 minutes). The results of the spiritual mindfulness intervention after nursing actions were carried out for 3 days, the nursing problem of anxiety was resolved. The patient experienced a change from initially the patient having an anxiety score of 80 (severe anxiety) to 40 (not anxious). Spiritual mindfulness intervention is effective in reducing anxiety so it can be used as an alternative to reduce anxiety in patients with chronic kidney failure.